(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Cal’ keeping agents is an on-call housekeeping service. Housekeeping refers to the management of duties and chores involved in the running of a household, such as cleaning, cooking, home maintenance, shopping, laundry, and bill payment. These tasks may be performed by members of the household or by other persons that are hired for this purpose. The researchers interviewed other establishments to observe how the business operates and becomes successful. Related studies on Cal’Keeping Agent had been conducted along with the industry review. The proponents also surveyed50 respondents where the proposed business will be established. A total of40%of the respondents may call the company twice a month,35% of the respondents responded once a month, 15% of the respondents replied once a week, and 10%of the respondents answered yearly. For the hour allocation in cleaning the house, 31%of the respondents answered that the average hours on cleaning per month for11–15 h, 28%of the respondents replied 5–10 h,17%of the respondents responded for 16–20 h,14%of the respondents responded for less than 5 h, and 10%of the respondents for more than 21h. The majority of the respondents’ expectation for finishing a cleaning session would be 3 h, while the least hour would be 5 h. Meanwhile, 45% of the respondents wanted to use a one-time cleaning session, 30%of the respondents said they wanted to use a deep cleaning session, and 25%of the respondents preferred to use a standard cleaning service. For price preference, 40% of the respondents can afford P800 for cleaning service,35%ofthe respondents were willing to pay P1,000, and 25% of the respondents were willing to pay P500. In terms of location viability, 65%of the respondents agreed that the business location in Sangandaan, Quirino Highway, Quezon Citywasappropriate. The most important factor for the respondents in choosing a cleaning company was the quality of service. Price was only a secondary factor for the respondents. The respondents called a the cleaning service once a month, while only 36%of the respondents needed service twice a week. The business will start at 8:00am and close at 9:00pm. In terms of the financial aspect, the business revenue was forecasted to have a 10% increase annually. There will be a growth in terms of expenses year on year. The changes in owners’ equity with a starting capital of P200,000 per partner will be added with the net income(P403,803.4), and the ending capital of the business will be the new capital for the second year of the business operation. The return on investment was expected to achieve its first-year operation by 32.35% and will follow by the next ROI per year.